The next generation of antiemetics for the management of postoperative nausea and vomiting. Issue 4 (December 2020) - Tan, Hon Sen; Dewinter, Geertrui; Habib, Ashraf S.
Abstract : Postoperative nausea and vomiting (PONV) afflict approximately 30% of patients overall and up to 80% of high-risk patients after surgery. Optimal pharmacological prophylaxis of PONV is challenging as it necessitates the consideration of PONV risk, drug efficacy, and potential adverse effects. Despite significant advances in our understanding of the pathophysiology and risk factors of PONV, its incidence has remained largely unchanged. Newer antiemetics have been introduced that may have improved safety profiles, longer duration of action, and better efficacy. This review aims to summarize the recent developments pertaining to these new agents and their potential application toward the management of PONV.